STRATEGI MANAJEMEN SUMBER DAYA MANUSIA: PENDEKATAN KONSEP - Amirullah Amirullah (Jurnal Akademika, 2005)
The strategic management of human resource widely is correlated with interaction and adaption, that emphasize: 1. the human resource management is totally integrated with strategy and the need company straegy; 2. the policy of human resources is closed to every subject of policy and interline; also 3. the holding of human resource activities is adapted, accepted and done by line manager as a part of daily activities. In accordance with management of human resources, the global that is supposed to be achieved by the company will have function to give a guidance about kinds of choices from human resoyrce activities which can give result ang strengthen the specific attitude needed to achieve the organization strategy.Key word; strattegy, human resource management